Carnosine supplementation and retinal oxidative parameters in a high-calorie diet rat model - Rogil Jose de Almeida Torres; Fernando Moreto; Andrea Luchini; Rogerio Joao de Almeida Torres; Sofia Pimentel Longo; Ricardo Aurino Pinho; Seigo Nagashima; Lucia de Noronha; Artur Junio Togneri Ferron; Carol Cristina Vagula de Almeida Silva; Camila Renata Correa; Giancarlo Aldini; et al. (BMC Ophthalmology, 2023)
Abstract Background To assess oxidative effects induced by a high-calorie diet on the retina of Wistar rats and test the antioxidative effects of carnosine supplementation. Methods Wistar rats were randomly divided into the following groups: standard diet (SD), high-calorie diet (HcD), standard diet + carnosine (SD + Car), and high-calorie diet + carnosine (HcD + Car). The body weight, adiposity index, plasma glucose, total lipids, high-density lipoprotein (HDL), low-density lipoprotein (LDL), uric acid, creatinine, and triglycerides of the animals were evaluated. The retinas were analyzed for markers of oxidative stress. Hydrogen peroxide production was assessed by 2',7'-dichlorodihydrofluorescein diacetate (DCF) oxidation. The total glutathione (tGSH), total antioxidant capacity (TAC), protein carbonyl, and sulfhydryl groups of the antioxidant system were analyzed. Results TAC levels increased in the retinas of the SD + Car group compared to the SD group (p < 0.05) and in the HcD + Car group compared to the HcD group (p < 0.05). The levels of GSH and the GSSH:GSSG ratio were increased in the HcD + Car group compared to the SD + Car group (p < 0.05). An increase in the retinal carbonyl content was observed in the HcD group compared to the SD group (p < 0.05) and in the HcD + Car group compared to the SD + Car group (p < 0.05). A high-calorie diet (HcD) was also associated with a decrease in retinal sulfhydryl-type levels compared to the SD group (p < 0.05). Conclusion The results suggest that feeding a high-calorie diet to rats can promote an increase in carbonyl content and a reduction in sulfhydryl groups in their retinas. The administration of carnosine was not effective in attenuating these oxidative markers. Trial registration Animal Ethics Committee of Botucatu Medical School - Certificate number 1292/2019.